Effects of the use of heather as anthelmintic in goats infected with Trichostrongylus colubriformis on ruminal fermentation and digestibility - Frutos P.; Hervás G.; Celaya R.; Moreno-Gonzalo J.; Rodríguez A.B.; García U.; Ferre I.; Ortega-Mora L.M.; Osoro K. (Challenging strategies to promote the sheep and goat sector in the current global context, 2011)
Previous field studies have supported the absence of a nutritional cost outweighing the beneficial anthelmintic effect of supplementing the diet of grazing goats with tannin-containing heather. In order to further research in this regard, an experiment was conducted indoors with 18 does artificially infected with Trichostrongylus colubriformis. The goats were offered lucerne hay for 6 weeks and then assigned to 3 treatments (diets): lucerne hay (L), 70 percent lucerne hay + 30 percent heather containing 64 g of tannic acid equivalents/kg DM (LH), and LH + polyethylene glycol (35 g PEG/animal and day; LH+PEG). Rumen fluid was obtained from each animal after 10 (period 1) and 36 (period 2) days, and afterwards total faecal output was collected for 5 days to assess gastrointestinal nematode egg excretion, and apparent digestibilities of DM and CP. Total daily faecal egg excretion was reduced in does consuming heather (491,216 for L vs 234,311 and 194,356 for LH+PEG and LH; P<0.05). Volatile fatty acid concentrations were greater in those animals (115 vs 102 vs 84 for LH, LH+PEG and L, respectively, P<0.05) but the use of PEG increased DM and CP digestibilities (P<0.05). In vitro gas production results suggest an adaptation of the rumen microbiota in goats supplemented with heather that was not reflected in differences between digestibility coefficients in periods 1 and 2. The fact that LH+PEG significantly improved the apparent digestibilities of DM (6 percent) and CP (13 percent) when compared to LH, but with both reducing egg excretion in the same proportion, might suggest that the threshold of tannins requested to obtain anthelmintic effects is probably quite low.
13. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2009/10/14-16, León (Spain)